Sin1 (Stress-Activated Protein Kinase-Interacting Protein) Regulates Ischemia-Induced Microthrombosis Through Integrin αIIbβ3-Mediated Outside-In Signaling and Hypoxia Responses in Platelets. Issue 12 (December 2018) - Xu, Yanyan; Ouyang, Xinxing; Yan, Lichong; Zhang, Mingliang; Hu, Zhenlei; Gu, Jianmin; Fan, Xuemei; Zhang, Lin; Zhang, Junfeng; Xue, Song; Chen, Guoqiang; Su, Bing; et al.
Abstract : Objective—: Microthrombosis as a serious consequence of myocardial infarction, impairs the microvascular environment and increases the occurrences of heart failure, arrhythmia, and death. Sin1 (stress-activated protein kinase-interacting protein) as an essential component of mTORC2 (mammalian target of rapamycin complex 2) is required for cell proliferation and metabolism in response to nutrients, stress, and reactive oxygen species and activates Akt and PKC (protein kinase C). However, the activation and function of Sin1/mTORC2 in ischemia-induced microthrombosis remain poorly understood. Approach and Results—: The phosphorylation of the mTORC2 target Akt at S473 (serine 473) was significantly elevated in platelets from the distal end of left anterior descending obstructions from patients who underwent off-pump coronary artery bypass grafting compared with platelets from healthy subjects. Consistent with this finding, phosphorylation of T86 in Sin1 was also dramatically increased. Importantly, the augmented levels of phosphorylated Sin1 and Akt in platelets from 61 preoperative patients with ST-segment—elevation myocardial infarction correlated well with the no-reflow phenomena observed after revascularization. Platelet-specific Sin1 deficiency mice and Sin1 T86 phosphorylation deficiency mice were established to explore the underlying mechanisms in platelet activation. Mechanistically, Sin1 T86 phosphorylation amplifies mTORC2-mediated downstream signals; it is also required for αIIbβ3-mediated outside-in signaling and plays a role in generating hypoxia/reactive oxygen species through NAD + /Sirt3 (sirtuin 3)/SOD2 (superoxide dismutase 2) pathway. Importantly, Sin1 deletion in platelets protected mice from ischemia-induced microvascular embolization and subsequent heart dysfunction in a mouse model of myocardial infarction. Conclusions—: Together, the results of our study reveal a novel role for Sin1 in platelet activation. Thus, Sin1 may be a valuable therapeutic target for interventions for ischemia-induced myocardial infarction deterioration. Abstract : Supplemental Digital Content is available in the text.